Effect of plant growth regulators on yield and quality of ber (Zizyphus mauritiana Lamk.) in semi-arid conditions (Indian Journal of Arid Horticulture, 2025)
The present investigation carried out to know the response of plant growth regulators on different cultivars of ber in semi-arid condition as prevailing high temperature and low humidity climatic situations in such regions are major hindrance of good yield. Experiment was conducted with 21 treatments and each treatment was replicated three times under Randomized Block Design. The experiment comprised three cultivars of ber viz., Gola, Kaithli and Umran and three plant growth regulators (NAA, 2,4-D and GA) with two concentration of each viz., 15 and 30 ppm and one control (water spray). The result showed that among PGRS spray of 2,4-D @ 30 ppm and among cultivars, cv. Umran exhibited significant influence on most of yield and quality parameters with maximum net return and B: C ratio except fruit weight, fruit diameter, TSS and sugars of ber fruits.
Keywords: PGRS; 2,4-D; quality